2022
DOI: 10.31331/sencenivet.v3i2.2149
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Orang Tua Dalam Pemenuhan Gizi Seimbang Sebagai Upaya Pencegahan Stunting Pada Anak Usia 4-5 Tahun

Abstract: Orang tua memiliki peranan yang sangat penting dalam pemenuhan gizi anak, agar anak dapat tumbuh dan berkembang secara optimal sesuai tahap usianya dan terhindar dari masalah gizi salah satunya stunting. Adapun tujuan penelitian: 1) untuk mengetahui peranan orang tua terhadap pemenuhan gizi seimbang sebagai upaya pencegahan stunting pada anak usia 4-5 tahun, 2) untuk mengetahui zat-zat gizi yang diperlukan dalam pemenuhan gizi seimbang untuk mencegah stunting pada anak usia 4-5 tahun, 3) untuk mengetahui peran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
3
Order By: Relevance
“…Namely, the child's height is lower or shorter (dwarf), and his body development is not normal occurs when children do not get the right amount of nutrition for a long time (chronic) (Giri et al, 2013). Signs and symptoms of stunting include the child's height not according to age, lower body weight not according to his age and slow cognitive development (Kementerian Kesehatan Republik Indonesia, 2022; Onis et al, 2018;and World Health Organization, 2014) The nutritional coverage that each individual must fulfil is in the form of macro-nutrients for the formation of energy, such as protein, carbohydrates and fats, as well as micronutrients, such as vitamins and minerals (Munawaroh et al, 2022). 2) Parenting is a series of things applied to nurture, care for, train, and guide.…”
Section: Study Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the child's height is lower or shorter (dwarf), and his body development is not normal occurs when children do not get the right amount of nutrition for a long time (chronic) (Giri et al, 2013). Signs and symptoms of stunting include the child's height not according to age, lower body weight not according to his age and slow cognitive development (Kementerian Kesehatan Republik Indonesia, 2022; Onis et al, 2018;and World Health Organization, 2014) The nutritional coverage that each individual must fulfil is in the form of macro-nutrients for the formation of energy, such as protein, carbohydrates and fats, as well as micronutrients, such as vitamins and minerals (Munawaroh et al, 2022). 2) Parenting is a series of things applied to nurture, care for, train, and guide.…”
Section: Study Reviewmentioning
confidence: 99%
“…The program prioritizes specific and sensitive nutritional management in the first 1000 days of life up to 6 years of age. Interventions include giving iron tablets during pregnancy, supplementary food for pregnant women, fulfilling nutrition, delivery at health workers, exclusive breastfeeding, complementary food for breastfeeding, complete primary immunization and vitamin A, as well as a clean and healthy lifestyle (Nahdlatul & Surabaya, 2019) Parents have an essential role in fulfilling children's nutrition in preventing stunting problems in children (Munawaroh et al, 2022). Furthermore, Saifah (2019) research revealed that the family has an important role in health promotion related to the introduction and provision of nutritious food and health practices in the family area.…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan ibu yang memiliki pendidikan rendah umumnya mengalami kesulitan dalam menerima informasi tentang kesehatan dan gizi anak. Akibatnya anak tidak mendapatkan makanan bergizi secara seimbang baik dari segi kualitas maupun kuantitas (Munawaroh, et al, 2022) Permasalahan gizi pada anak usia sekolah diakibatkan oleh perilaku makan yang kurang baik, yakni karena tepat atau pemilihan jenis makanan yang berlebihan (Alleander & Spradley, 2005). Umumnya orang tua hanya memberikan dua jenis makanan dalam setiap kali makan, misalnya nasi dengan sayur atau satu jenis lauk.…”
Section: Pendahuluanunclassified
“…Kurangnya kreativitas orang tua dalam memberikan keanekaragaan makanan membuat anak lebih mudah bosan dengan makanan yang diberikan. (Munawaroh, et al, 2022) Salah satu pihak yang dapat berperan dalam menentukan perilaku gizi anak adalah peran keluarga (Green & Kreuter, 2005). Peran keluarga dalam menjaga gizi anak adalah dengan menerapkan sarapan pagi sebelum berangkat sekolah.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation